Recent Advances on Synthetic and Polysaccharide Adhesives for Biological Hemostatic Applications - Li, Dawei; Chen, Jing; Wang, Xing; Zhang, Mingming; Li, Chunlin; Zhou, Jin (Frontiers in Bioengineering and Biotechnology, 2020)
Rapid hemostasis and formation of stable blood clots are very important to prevent massive blood loss from the excessive bleeding for living body, but their own clotting process cannot be completed in time for effective hemostasis without the help of hemostatic materials. In general, traditionally suturing and stapling techniques for wound closure are prone to cause the additional damages to the tissues, activated inflammatory responses, short usage periods and inevitable second operations in clinical applications. Especially for the large wounds that require the urgent closure of fluids or gases, these conventional closure methods are far from enough. To address these problems, various tissue adhesives, sealants and hemostatic materials are placed great expectation. In this review, we focused on the development of two main categories of tissue adhesive materials: synthetic polymeric adhesives and naturally derived polysaccharide adhesives. Research of the high performance of hemostatic adhesives with strong adhesion, better biocompatibility, easy usability and cheap price is highly demanded for both scientists and clinicians, and this review is also intended to provide a comprehensive summarization and inspiration for pursuit of more advanced hemostatic adhesives for biological fields.